A Student-Informed Guide for Success on the OB/GYN Clerkship - Naeema Hopkins-Kotb; Hannan Sylla; Anna Krotinger; Andrea Pelletier; Deborah A. Bartz; Natasha R. Johnson (Journal of Medical Education and Curricular Development)
The obstetrics and gynecology (OB/GYN) clerkship is a uniquely enriching and challenging rotation for medical students. Available literature prepares students for medicine and surgery clerkships, but few guides identify and discuss the unique characteristics of OB/GYN that impact student learning and performance during the clerkship. Here, we aim to highlight the specific clinical learning environments, emotionally sensitive experiences, and technical performance expectations that students should anticipate and be prepared for in the OB/GYN clerkship. We believe all students benefit from learning these skills to care for their future patients no matter their chosen specialty.